2016
DOI: 10.1016/j.juro.2016.01.106
|View full text |Cite
|
Sign up to set email alerts
|

Role of PAR2 in the Development of Lower Urinary Tract Dysfunction

Abstract: Purpose Lower urinary tract symptoms are a common finding in patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). We reported that the mast cell-tryptase-PAR2 axis plays a critical role in the development of chronic pain in experimental autoimmune prostatitis (EAP), a mouse model of CP/CPPS. We therefore examined whether PAR2 activation mediates lower urinary tract dysfunction. Materials and Methods Functional cystometry was used in male B6 mice along with immunoblots and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…In the murine EAP model of CP/CPPS, there is also increased expression of PAR2 and these mice have associated urinary dysfunction. When PAR2 is neutralized with antibodies, it normalizes voiding frequency and bladder capacity in these CP/CPPS animals . Therefore, based on these studies and our current findings, we think that the limited efficacy of α‐blockers in treating voiding symptoms in patients of CP/CPPS may be due to activation of non‐adrenergic receptors, such as PAR2, which can initiate smooth muscle contractions as α‐adrenergic receptors themselves.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In the murine EAP model of CP/CPPS, there is also increased expression of PAR2 and these mice have associated urinary dysfunction. When PAR2 is neutralized with antibodies, it normalizes voiding frequency and bladder capacity in these CP/CPPS animals . Therefore, based on these studies and our current findings, we think that the limited efficacy of α‐blockers in treating voiding symptoms in patients of CP/CPPS may be due to activation of non‐adrenergic receptors, such as PAR2, which can initiate smooth muscle contractions as α‐adrenergic receptors themselves.…”
Section: Discussionsupporting
confidence: 50%
“…When PAR2 is neutralized with antibodies, it normalizes voiding frequency and bladder capacity in these CP/CPPS animals. 7,16 Therefore, based on these studies and our current findings, we think that the limited efficacy of α-blockers in treating voiding symptoms in patients of CP/CPPS may be due to activation of non-adrenergic receptors, such as PAR2, which can initiate smooth muscle contractions as α-adrenergic receptors themselves. In fact, Hennenberg et al 38 have alluded to this possibility when they showed that in human prostate tissue endothelin-1 can induce smooth muscle contraction and induce contractile forces that have similar magnitude to those caused by noradrenaline.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Regarding the functional part of the study, we measured only voiding behavior. Additional methodologies such as cystometry or measuring contractility should be included in further studies because EAP in C57BL/6J mice is reported to induce increased voiding frequency and decreased bladder capacity as determined by cystometry . In the present study, we focused on the characterization of two prostatitis models by voiding behavior and chronic pelvic pain.…”
Section: Discussionmentioning
confidence: 99%